RELEVANSI KOMPETENSI KEPRIBADIAN PENDIDIK PERSPEKTIF TAFSIR ASY-SYARAWI SURAH LUQMAN AYAT 13-19 - Muhammad Irsyad; Sharikhul Hanif; Suci Saharani (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
One part of the verses of the al-Qur’an contains Tarbiyah, namely education, including how to teach in the al-Qur’an. An educator must have competence in educating students during the learning process. This study will discuss how the personality competencies of educators are contained in the al-Qur’an in Surah Luqman verses 13-19 by referring to the Asy-Sya'rawi interpretation. The author uses qualitative research methods. In this study, using the type of library/ library research and content analysis approach. Therefore, the author collects the personality competencies of educators contained in the Asy-Syarawi tasfir in the al-Quran Surah Luqman verses 13-19. The author found that there are 10 personality competencies of educators contained in Tafsir Asy-Syarawi in Surah Luqman verses 13-19.